2022
DOI: 10.1039/d1cc06341c
|View full text |Cite
|
Sign up to set email alerts
|

Refining boron–iodane exchange to access versatile arylation reagents

Abstract: Aryl(Mes)iodonium salts, which are multifaceted aryl transfer reagents, are synthesized via boron-iodane exchange. Modification to both the nucleophilic (aryl boron) and electrophilic (mesityl-λ3-iodane) reaction components result in improved yield and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Acyclic diaryliodonium salts are readily synthesized from simple building blocks and therefore have the potential to provide efficient access to a wide range of arynes. 13 However, the inherent inertness of acyclic diaryliodonium salts to deprotonation with weak base is a significant hurdle, 11 a , d , g and recent work has used a neighbouring sulfonyloxy group as an activator to address this challenge. 11 h , i Our efforts focused on substrate 1a bearing a chloro-substituent, which is less inductively withdrawing that a triflyl group, 14 and we identified a set of reaction conditions that generated and trapped an aryne in moderate yield with furan 2a (Scheme 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Acyclic diaryliodonium salts are readily synthesized from simple building blocks and therefore have the potential to provide efficient access to a wide range of arynes. 13 However, the inherent inertness of acyclic diaryliodonium salts to deprotonation with weak base is a significant hurdle, 11 a , d , g and recent work has used a neighbouring sulfonyloxy group as an activator to address this challenge. 11 h , i Our efforts focused on substrate 1a bearing a chloro-substituent, which is less inductively withdrawing that a triflyl group, 14 and we identified a set of reaction conditions that generated and trapped an aryne in moderate yield with furan 2a (Scheme 2a).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the feasibility of coupling two stages, boron–iodane exchange and aryne formation/trapping, together in a one-pot formal dehydroboration reaction (Table ). Although both stages have literature precedent, , there are several potential incompatibilities. For instance, in prior reports on the individual stages, different solvents are used, and (Lewis or Bronsted) acid conditions are used in stage 1, whereas basic conditions are used in stage 2. , We first attempted to mitigate these incompatibilities by conducting a solvent swap between each stage without actually isolating the intermediate aryl­(Mes)­iodonium salt.…”
mentioning
confidence: 99%
“…Although both stages have literature precedent, , there are several potential incompatibilities. For instance, in prior reports on the individual stages, different solvents are used, and (Lewis or Bronsted) acid conditions are used in stage 1, whereas basic conditions are used in stage 2. , We first attempted to mitigate these incompatibilities by conducting a solvent swap between each stage without actually isolating the intermediate aryl­(Mes)­iodonium salt. By using p -chlorophenylboron 1a , we observed higher yields with the potassium trifluoroborate salt relative to the boronic acid when MeCN was used for the first stage and TBME was used for the second stage (Table , entries 1 and 2). , We also attempted to conduct the entire telescoped reaction in the same solvent using either MeCN or TBME, and we found that TBME resulted in substantially higher yield than MeCN as solvent (Table , entries 3 and 4).…”
mentioning
confidence: 99%